Factors Shaping Exports of Cultural Goods from Pakistan - SABA SALIM; ZAFAR MAHMOOD (NUST Journal of Social Sciences and Humanities, 2021)
In the era of economic globalization, cultural goods trade has assumed a vital role in overall bilateral trade. It has become an emerging and transformative force behind socio-cultural-economic development and an important source of inclusive growth. Once virtually unlocked, trade in cultural goods is now fast growing with world-wide market openings. Trade liberalisation in cultural goods thus needs to be treated as a priority policy issue in multilateral and regional trade negotiations. Despite large potential of exports in cultural goods, Pakistan has been unsuccessful in realizing it. This is mainly because of lack of due attention given to it by the policymakers. In this regard, this paper makes a beginning to investigate the determinants of cultural goods exports from Pakistan for the period 2003-2012 with its 157 trading partner countries. The Gravity model is used to identify factors that determine exports of cultural goods. Six major categories of cultural goods are used for the purpose of estimation. Results indicate that size of Pakistan and its trading partner countries’ markets as well as distance among them are important determinants of exports in cultural goods. Specifically, cultural goods exports are strongly and positively influenced by the growth of the GDP in Pakistan, while the trading partner countries’ GDP growth negatively influence cultural goods’ exports. Distance, representing transaction costs and trade barriers, negatively affect exports of cultural goods; while colonial ties, common language, common border and land area of the trading partners positively influence the export of cultural goods. Exports of cultural goods to landlocked countries are lower than other trading partner countries.